2021
DOI: 10.3390/su13084528
|View full text |Cite
|
Sign up to set email alerts
|

The Model of Vehicle and Route Selection for Energy Saving

Abstract: The World Bank, United Nations, the Organization for Economic Cooperation and Development, and others are in line with the governments of countries that are strongly interested in the sustainable development of countries, regions, and enterprises. One of the aspects that affects the indicators and prospects of sustainable development is the efficiency of energy source use. Nationwide reductions in the greenhouse gas emissions of motor vehicles could have a direct effect on ambient temperature and reducing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
(153 reference statements)
0
1
0
Order By: Relevance
“…For sustainable green supply chains, [47] employed cases and found that a vertically integrated supply chain can help improve car production. [48] focused on the model of vehicle and route selection. [49] considered the repair and maintenance part.…”
Section: Discussionmentioning
confidence: 99%
“…For sustainable green supply chains, [47] employed cases and found that a vertically integrated supply chain can help improve car production. [48] focused on the model of vehicle and route selection. [49] considered the repair and maintenance part.…”
Section: Discussionmentioning
confidence: 99%